2004
DOI: 10.1038/ni1028
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 signals after translocating from the ER to CpG DNA in the lysosome

Abstract: Microbial DNA sequences containing unmethylated CpG dinucleotides activate Toll-like receptor 9 (TLR9). We have found that TLR9 is localized to the endoplasmic reticulum (ER) of dendritic cells (DCs) and macrophages. Because there is no precedent for immune receptor signaling in the ER, we investigated how TLR9 is activated. We show that CpG DNA binds directly to TLR9 in ligand-binding studies. CpG DNA moves into early endosomes and is subsequently transported to a tubular lysosomal compartment. Concurrent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
1,078
5
12

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,228 publications
(1,144 citation statements)
references
References 35 publications
49
1,078
5
12
Order By: Relevance
“…10 It has also been shown that the loss of surface membrane of phagocytes occurring during particle internalization is substituted by the ER. 11 Therefore, ER membrane is a prime candidate for the supplementation of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It has also been shown that the loss of surface membrane of phagocytes occurring during particle internalization is substituted by the ER. 11 Therefore, ER membrane is a prime candidate for the supplementation of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the ER is punctually associated with the plasma membrane 10 and that it substitutes the loss of plasma membrane during the process of particle ingestion. 11 In recent publications, we and others showed that cells undergoing apoptosis change the glycosylation status of their membranes.…”
mentioning
confidence: 99%
“…Plasmacytoid DCs show high levels of constitutive IRF7 expression, relative to monocyte-derived DCs [53], and two concomitant reports showed that Myd88 forms a complex with IRF7 to trigger its activation and induce IFN-a [54,55]. TLR7 and TLR9 are located primarily in the intracellular endosomal compartment [56,57] and the Myd88-IRF7 interaction takes place in the endosomal vesicles of the plasmacytoid DCs [58] (Figure 2). The complex must remain in the endosome for a prolonged time period and resist transfer to lysosomal vesicles to trigger activation of IRF7 [58].…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 92%
“…The peritoneal macrophages were primed and stimulated as described in MATERIALS AND METHODS. GM-130, calnexin, α-tubulin, early endosome antigen 1 (EEA1), vimentin, and γ-tubulin were used as markers of Golgi apparatus, endoplasmic reticulum, microtubule, endosome, phagosome, and centromere, respectively (Webb et al, 2001;Latz et al, 2004;Eng et al, 2007;David et al, 2010;Wolff et al, 2011;Yuan et al, 2012). Lysotracker was applied for lysosome detection.…”
Section: Asc Pyroptosome Did Not Co-localize With Other Detected Orgamentioning
confidence: 99%